2018
DOI: 10.1111/arcm.12397
|View full text |Cite
|
Sign up to set email alerts
|

Defining and Characterizing Archaeological Quartzite: Sedimentary and Metamorphic Processes in the Lithic Assemblages of El Habario and El Arteu (Cantabrian Mountains, Northern Spain)

Abstract: Quartzite was the second most‐often used lithic raw material in Europe in the Palaeolithic. However, this rock has not been characterized fully from the geo‐archaeological point of view. This study characterizes, defines and determines types of quartzite in northern Spain through a methodology that integrates petrography, digital image processing and X‐ray fluorescence. As a methodological foundation for the characterization of the material, it aims to open the possibility of discovering mechanisms of mobility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…The quantification of textural data could potentially be used to create dendrograms to better understand the relationships between textures and minerals (e.g. Prieto et al 2019). Further research will be required to determine whether textural characteristics may be used as sourcing criterion for quartzites.…”
Section: Chapter 72 Methodological Considerations: a Look Aheadmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantification of textural data could potentially be used to create dendrograms to better understand the relationships between textures and minerals (e.g. Prieto et al 2019). Further research will be required to determine whether textural characteristics may be used as sourcing criterion for quartzites.…”
Section: Chapter 72 Methodological Considerations: a Look Aheadmentioning
confidence: 99%
“…Magmatic rocks were classified according to their essential, type, accessory, and postmagmatic minerals (sensu Gill 2010) artifacts undertaken in a recent study have found this to be of little value to identify varieties other than to determine the extent to which a sample was metamorphosed (Prieto et al 2019). Streckeisen 1976).…”
Section: Thin Section Analysismentioning
confidence: 99%
“…This is especially important in those areas where flint is not common or in ancient chronologies in areas where nonflint rocks are predominant. However, in recent years, quartzite from archaeological deposits has been studied from geoarchaeological perspectives by combining different destructive methodologies such as petrographic analysis and geochemical procedures (Blomme et al 2012;Cnudde et al 2013;Dalpra and Pitblado 2016;Pitblado et al, 2008Pitblado et al, , 2012Prieto et al 2019;Veldeman et al 2012). These studies reflect the ambiguity of the term quartzite in archaeological literature, where it can refer to different geological origins, from clearly metamorphic to sedimentary.…”
Section: Both Perspectives Converge In the Characterisation Of Obsidianmentioning
confidence: 99%
“…To this end, we have analysed the lithic collections from El Arteu and El Habario, two Middle-Palaeolithic sites situated in the Central part of the Cantabrian Region, northern Spain. We summarise the main results derived from the petrographic and geochemical characterisation of 18 samples recently published by our research group (Prieto et al 2019), but especially, we will focus on non-destructive criteria to characterise the lithic surfaces of quartzites using stereoscope microscopy and descriptive characterisation. The diagenetic and metamorphic changes which modify the texture and structure of former sedimentary rocks, the grain size and its distribution, and the mineral component itself will be analysed in this research using both approaches.…”
Section: Both Perspectives Converge In the Characterisation Of Obsidianmentioning
confidence: 99%
“…The analysis is especially focused on the quar$ ite, a rock which constitutes approximately 80% of the assemblage. To analyse this material, we applied a methodological approach that combines petrographic characterisation, X-Ray fl uorescence and stereomicroscopy using the same protocol proposed in the region by our team (Prieto et al, 2019;Prieto et al, 2020). This procedure allows us to characterise and assign each lithic fragment to a petrogenetic type of quar$ ite using a solid geoarchaeological basis.…”
Section: Andreas Pastoors Episodes Of Magdalenian Hunter-gatherers Inmentioning
confidence: 99%